Cobalt(ii) complexes with the quinolone antimicrobial drug oxolinic acid: structure and biological perspectives1. Issue 46 (23rd May 2015) - Irgi, Evgenia P.; Geromichalos, George D.; Balala, Sofia; Kljun, Jakob; Kalogiannis, Stavros; Papadopoulos, Athanasios; Turel, Iztok; Psomas, George
<x xml:space="preserve">Abstract</x> The interaction of cobalt(ii)–oxolinato complexes with DNA and albumins was investigated with spectroscopic and physicochemical techniques and molecular docking calculations.